2019
DOI: 10.1111/1462-2920.14501
|View full text |Cite
|
Sign up to set email alerts
|

Viral transmission in honey bees and native bees, supported by a global black queen cell virus phylogeny

Abstract: Summary In recent decades, we have realized that honey bee viruses are not, in fact, exclusive to honey bees. The potential impact of Apis‐affiliated viruses on native pollinators is prompting concern. Our research addresses the issue of virus crossover between honey bees and native bees foraging in the same localities. We measured the presence of black queen cell virus (BQCV), deformed wing virus (DWV) and sacbrood virus (SBV) in managed Apis mellifera (honey bees) and native Andrena spp. (subgenus Melandrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 57 publications
3
34
1
Order By: Relevance
“…To understand the current epidemic of bee viruses, it is key to determine the role of the host species and geographic distribution [12,65]. By placing the sequences generated in this study within a global phylogeny, we found that both KBV and DWV showed strong grouping by geographic regions.…”
Section: Global Distribution and Evolution Of Bee Virusesmentioning
confidence: 85%
See 2 more Smart Citations
“…To understand the current epidemic of bee viruses, it is key to determine the role of the host species and geographic distribution [12,65]. By placing the sequences generated in this study within a global phylogeny, we found that both KBV and DWV showed strong grouping by geographic regions.…”
Section: Global Distribution and Evolution Of Bee Virusesmentioning
confidence: 85%
“…Viral infections have been extensively studied in the European honey bee (Apis mellifera) because a number of RNA viruses that are circulating within bee populations have been associated with reduced health and reports of colony collapses [8,9]. Increasing evidence suggests that many of these pathogens are not specific to honey bees and instead are shared between many pollinator species and associated arthropods, including bumble bees and other wild bees [10][11][12]; bee predators, such as wasps [10,11]; and scavenging insects, such as ants, cockroaches, and beetles [10,[13][14][15]. Many of these host species have been found cohabiting in bee hives [13,15,16] or share floral resources with honey bees [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the most commonly occurring honey bee-associated viruses include Deformed wing virus (DWV), Black queen cell virus (BQCV), Israeli acute paralysis virus (IAPV), Acute bee paralysis virus (ABPV), Kashmir bee virus (KBV), and Sacbrood virus (SBV) 2 . Although the above listed are commonly referred to as honey bee viruses, previous research has detected these viruses in a number of other arthropods including the ectoparasitic mite Varroa destructor 3,4 , other insect pollinators such as hoverflies, bumblebees, and solitary bees [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] , and other Hymenopteran insects including some wasps and ants 15,20-28 . Both direct and indirect interactions between honey bees and some of these arthropods (e.g., foraging at the same floral resource, parasitism, and predation) have been proposed as possible routes in which interspecies transmission of honey bee-associated viruses can occur 29-32 .In the southern United States, ants are ubiquitous within apiaries and are common pests of managed honey bees 33 .…”
mentioning
confidence: 99%
“…Our experiment examined within-species transmission, but, as noted above, in the wild bumblebees live in complex multispecies assemblages of floral visitors. An increasing number of studies suggest that between-species transmission, in particular from managed honeybees, may be driving emergent diseases in wild pollinators [30,33,34,45,56,57,[63][64][65]. As such, the next obvious step would be to conduct controlled semi-field trials to understand transmission dynamics of viruses between honeybees and bumblebees [34].…”
Section: Discussionmentioning
confidence: 99%